Effectiveness of the Family Hope Program in Improving Household Welfare in Kupang City - Kriatian D. Rupindara; Fredrik Lukas Benu; Hamza Huri Wulakada (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The Family Hope Program (Program Keluarga Harapan/PKH) is Indonesia's primary conditional cash transfer (CCT) scheme for poverty alleviation. This study examines PKH effectiveness in improving household welfare among beneficiaries in Oebobo District, Kupang City, East Nusa Tenggara (NTT), employing a Three-Stage Least Squares (3SLS) simultaneous equation approach. The analysis integrates a Gender Equality, Disability, and Social Inclusion (GEDSI) perspective to evaluate Access, Participation, Control, and Benefit (APCB) dimensions for vulnerable groups. A mixed-methods explanatory sequential design was applied to 151 beneficiary households selected via proportional sampling across three urban sub-districts. The 3SLS estimations establish that targeting accuracy (X1) and economic empowerment (X3) are the most significant determinants of PKH effectiveness; PKH effectiveness (Y1) strongly shapes household governance (Y2) through the Family Capacity Building Meetings (P2K2) mechanism; and PKH effectiveness is the dominant determinant of household welfare (Y3), with a near-unity coefficient (β=0.97). GEDSI analysis reveals that female-headed households, the elderly, and persons with disabilities face compounding vulnerabilities inadequately addressed by current program design. The study recommends strengthening data verification systems, embedding economic empowerment as a core pillar, and adopting differentiated targeting based on intersectional vulnerability profiles.